Aqueous extraction of seed oil from mamey sapote (Pouteria sapota) after Viscozyme L treatment - Tacias-Pascacio, Veymar G. (2021)
In this study, aqueous enzymatic extraction (AEE) was evaluated during the process of obtaining oil from mamey sapote seed (OMSS). Viscozyme L enzyme complex was used at pH 4 and 50 ◦C during the optimization of the extraction process by central composite design and response surface methodology. Optimal conditions were: 3.5% (w/w) of enzyme (regarding the seed weight), 5.5 h of incubation time, 235 rpm of agitation rate, and 1:3.5 of solid-to-liquid ratio. These conditions enabled us to obtain an OMSS yield of 66%. No statistically significant differences were found in the fatty acid profile and physicochemical properties, such as the acid and iodine values and the percentage of free fatty acids, between the oil obtained by AEE or by the conventional solvent extraction (SE). However, the oxidative stability of the oil obtained by AEE (11 h) was higher than that obtained by SE (9.33 h), therefore, AEE, in addition to being an environmentally friendly method, produces a superior quality oil in terms of oxidative stability. Finally, the high oil content in mamey sapote seed, and the high percentage of oleic acid (around 50% of the total fatty acid) found in this oil, make it a useful edible vegetable oil.